Improving Knowledge Structure through Extended Scratch-Build Concept Mapping - Prasetya, Didik Dwi; Hayashi, Yusuke; Hirashima, Tsukasa (Universitas Negeri Malang, 2020)
Extended concept mapping is a potential technique to elicit missing ideas and relationships. This study explored an Extended Scratch-Build (ESB) concept mapping in improving learners' knowledge structure. ESB is an expansion of an open-ended approach that asks students to connect the prior-existing original concept map with the new additional map on related material topics. The practical use of ESB has been conducted and proves positive effects on learning achievements. However, no information has been provided regarding the performance of the concept map components that describe the broad overview of students' attainments. This observationalÂ study focused on improving learners' knowledge using quantity measurements based on concept map features, consists of a number of concepts, number of links, and a number of propositions. University students (N = 27) with a major in Informatics Engineering participated in the study. The results reported that students' knowledge structure on additional maps significantly increased compared to the prior original map.